2021
DOI: 10.1038/s41598-021-00324-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profile of mesothelial exosomes isolated from peritoneal dialysis effluent of children with focal segmental glomerulosclerosis

Abstract: Peritoneal dialysis (PD) is the worldwide recognized preferred dialysis treatment for children affected by end-stage kidney disease (ESKD). However, due to the unphysiological composition of PD fluids, the peritoneal membrane (PM) of these patients may undergo structural and functional alterations, which may cause fibrosis. Several factors may accelerate this process and primary kidney disease may have a causative role. In particular, patients affected by steroid resistant primary focal segmental glomeruloscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…According to our extensive analysis, the morphology, size distribution, as well as the protein-to-lipid ratio of the isolated PDE-EVs corresponded to typical EVs (Figure 2). Moreover, PDE-EVs were positive for the known EV-specific proteins, including annexin, CD9, CD63, HSP70, and for E-cadherin and CK-18, which is consistent with the previous work by Bruschi et al [16], Corciulo et al [17], and Huang et al [33], suggesting that the isolated PDE-EVs are of the mesothelial origin (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…According to our extensive analysis, the morphology, size distribution, as well as the protein-to-lipid ratio of the isolated PDE-EVs corresponded to typical EVs (Figure 2). Moreover, PDE-EVs were positive for the known EV-specific proteins, including annexin, CD9, CD63, HSP70, and for E-cadherin and CK-18, which is consistent with the previous work by Bruschi et al [16], Corciulo et al [17], and Huang et al [33], suggesting that the isolated PDE-EVs are of the mesothelial origin (Figure 2).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that PD effluent-derived EVs are positive for the mesothelial marker mesothelin, supporting that mesothelial cells may be one of the sources of these EVs (Bruschi et al, 2021;Fang et al, 2022). However, using single cell marker to determine the source of PD effluent-derived EVs is not sufficient, and the specific cell sources of these EVs remain largely unknown.…”
Section:  Discussionmentioning
confidence: 99%
“…Our first comprehensive proteomic analysis assayed mesothelial sEVs from peritoneal dialysis (PD) effluent of subjects affected by FSGS, in comparison to subjects bearing other KDs. PTP4A1 was the most statistically significant biomarker associated with PD vintage and loss of peritoneal membrane function, caused by peritoneal fibrosis, due to the unphysiological composition of PD fluids [ 82 ]. As peritoneal fibrosis is a frequent evolution of PD, which can limit the efficacy of dialytic treatment [ 82 ], it would be useful to validate PTP4A1 as a prognostic biomarker to predict the progression of renal fibrosis in PD.…”
Section: Extracellular Vesicles As Biomarker Source In Glomerular Dis...mentioning
confidence: 99%
“…PTP4A1 was the most statistically significant biomarker associated with PD vintage and loss of peritoneal membrane function, caused by peritoneal fibrosis, due to the unphysiological composition of PD fluids [ 82 ]. As peritoneal fibrosis is a frequent evolution of PD, which can limit the efficacy of dialytic treatment [ 82 ], it would be useful to validate PTP4A1 as a prognostic biomarker to predict the progression of renal fibrosis in PD. ANXA13, the founder member of the annexin (ANX) family, was able to distinguish with 100% accuracy sEVs from PD effluent from FSGS patients versus those without FSGS [ 103 ].…”
Section: Extracellular Vesicles As Biomarker Source In Glomerular Dis...mentioning
confidence: 99%